2001
DOI: 10.1287/trsc.35.2.148.10136
|View full text |Cite
|
Sign up to set email alerts
|

A Cell-Based Traffic Control Formulation: Strategies and Benefits of Dynamic Timing Plans

Abstract: This study developed a dynamic traffic-control formulation that considers the entire Fundamental Diagram. This incorporation of the Fundamental Diagram is especially important for modeling oversaturated traffic. For this purpose, traffic is modeled after the cell-transmission model (CTM), which is a convergent numerical approximation to the hydrodynamic model. We transformed CTM to a set of mixed-integer constraints and subsequently cast the dynamic signal-control problem to a mixed-integer linear program. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
86
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 211 publications
(87 citation statements)
references
References 13 publications
1
86
0
Order By: Relevance
“…In comparison to other higher order traffic flow models, CTM has lesser number of output variables and input parameters which qualifies CTM as a suitable model for real-time applications. CTM has been used for traffic state estimation (Munoz et al 2003;Munoz et al 2006;Gang, Jiang, and Cai 2007;Tampere andImmers 2007, Long et al 2008;Long et al 2011) as well as for DTA applications of traffic network optimization (Lo 1999, Ziliaskopoulos 2000, Lo 2001, Gomes and Horowitz 2006, Liu, Lai and Gang 2006, Chiu et al 2007). …”
Section: Research Methodsologymentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison to other higher order traffic flow models, CTM has lesser number of output variables and input parameters which qualifies CTM as a suitable model for real-time applications. CTM has been used for traffic state estimation (Munoz et al 2003;Munoz et al 2006;Gang, Jiang, and Cai 2007;Tampere andImmers 2007, Long et al 2008;Long et al 2011) as well as for DTA applications of traffic network optimization (Lo 1999, Ziliaskopoulos 2000, Lo 2001, Gomes and Horowitz 2006, Liu, Lai and Gang 2006, Chiu et al 2007). …”
Section: Research Methodsologymentioning
confidence: 99%
“…In their method, they assumed availability of data from measurement sensors and only utilized these measurements, without using any kind of traffic flow model. Lo (2001) proposed a method for determining dynamic signal control timing plans based on system optimal principle using CTM based network model, which optimize network performance by keeping the density at an optimum level so as to ensure maximum flow on all links approaching a signalized intersection. The results indicated that green progression could reduce delays on the network.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Daganzo (1994) proposed a cell transmission model (CTM) that adopted a convergent approximation to the LWR model to evaluate the traffic on a highway network with a single entrance and exit. Afterwards, more cell types are applied in CTM to broaden its applicability (Daganzo 1995;Lo 1999;Lo 2001;Lo, Chang et al 2001). METANET (Messmer and Papageorgiou 1990) considered the situation of a motorway network based on the secondorder model.…”
Section: Introductionmentioning
confidence: 99%
“…(1) store-and-forward models (Hakimi, 1969;Singh and Tamura, 1974;D'Ans and Gazis, 1976), (2) disper sion-and-store models (Cremer and Schoof, 1989;Chang et al, 1994), and (3) kinematic wave models (Ste phanedes and Chang, 1993;Lo, 2001).…”
Section: Introductionmentioning
confidence: 99%